Understanding of income and race disparities in hurricane evacuation is contingent upon study case and design - Harsh Anand; Samarth Swarup; Majid Shafiee-Jood; Negin Alemazkoor (Scientific Reports)
Abstract As hurricanes become more frequent and destructive, understanding evacuation decision-making is crucial to refining disaster response strategies. Several studies have explored how socioeconomic characteristics such as income and race impact evacuation behavior. Most of these studies focus on a single hurricane event with the geographic extent limited to one or two states, each using a distinct study design, making them difficult to compare. This raises the question of whether findings from isolated cases can be generalized across different hurricane scenarios and geographical settings under a similar study design and consistent parameter definitions. To address this gap, in this study, we conduct a comparative analysis to understand income and racial disparity across multiple hurricane events. The results indicate that, even with a consistent study design, disparities in evacuation among different socioeconomic groups vary on a case-by-case basis. Furthermore, we show that the study design significantly impacts the observed trends within a single case. This highlights the importance of avoiding generalized conclusions based on limited case studies. It further emphasizes how flawed study designs may fail to capture the complexities of real-world behaviors, thereby leading to suboptimal or ineffective policy recommendations or designs.